Gender, Identity, and Islam: An Overview (American Journal of Islam and Society, 2010)
Books Reviewed: Valentine M. Moghadam, ed., From Patriarchy to Empowerment:Women’s Participation, Movements, and Rights in the Middle East,North Africa, and South Asia. Syracuse, NY: Syracuse University Press,2007; Ida Lichter, Muslim Women Reformers: Inspiring Voices againstOppression. Amherst, NY: Prometheus Books, 2009; Wahida Shaffi, ed.,Our Stories, Our Lives: Inspiring Muslim Women’s Voices. Bristol, UK: ThePolicy Press for the Joseph Rowntree Foundation, 2009.The realm of gender studies is rife with potential research foci: to comprisethe geographical, political, and ethical breadth that spans North Africa toSouth Asia, war novels and Iranian cinema to dowries and hudud is, then,a veritable feat. Assuming the concept of patriarchy as the nexus fromwhich to assess the multidimensional subjugation of women within thepolitical, socioeconomic, and ethnic spheres, Valentine M. Moghadamaffords a sweeping, yet insightful, collection of nineteen articles originatingfrom the “Women in the Global Community” conference hosted in Istanbulby the Fulbright Commission in September 2002 ...